Intellectual structure of Korean theology 2000–2008: Presbyterian theological journals. (June 2013) - Yoo, Yeong Jun; Lee, Jae Yun; Choi, Sanghee
A bibliometric analysis of author keywords in articles from nine Korean theological journals published from 2000 to 2008 found 10 clusters that represent the intellectual structure of Korean theology. Three main streams of Korean theology studies were identified: Reformed theology, general theology, and evangelicalism. The intellectual structures of the representative journal for each stream were examined in depth. To visualize these intellectual structures, we used co-word analysis and a Pathfinder network (PFnet) algorithm. The Pathfinder network was constructed by two approaches: first-order cosine coefficients and second-order correlation coefficients. Semantic review of the results suggests that second-order correlation coefficients more effectively present the intellectual structure of a domain by PFnet.